Determination of a nonlinear source term in a diffusion equation with final observations - Gongsheng Li; Yichen Ma; Kaitai Li (International Journal of Mathematics and Mathematical Sciences)
This paper deals with an inverse problem of determining a nonlinear source term in a quasilinear diffusion equation with overposed final observations. Applying integral identity methods, data compatibilities are deduced by which the inverse source problem here is proved to be reasonable and solvable. Furthermore, with the aid of an integral identity that connects the unknown source terms with the known data, a conditional stability is established.